2019
DOI: 10.1002/kjm2.12058
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CMTM7 inhibits cell growth and migration in liver cancer

Abstract: Chemokine‐like factor (CKLF)‐like, MAL and related proteins for vesicle trafficking and membrane link (MARVEL) transmembrane domain‐containing family proteins (CMTMs) have significant roles in the immune system, in male reproduction, as well as in tumorigenesis. Previous studies have shown that CMTM family member 7 (CMTM7) was broadly expressed in various normal tissues, but not in lung, gastric, esophageal, pancreas, and cervix cancers. To explore its relationship with liver cancer, we examined the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…40 When liver cancer SK-Hep -1 cells were over-expressed with CMTM7, the expression of E-cadherin protein was increased and N-cadherin protein was decreased, indicating CMTM7 had a migration-suppressive ability. 41 The positive correlation between the expression of CMTM2 and E-cadherin in our study further confirms the role of CMTM members in cancer metastasis.…”
Section: Discussionsupporting
confidence: 82%
“…40 When liver cancer SK-Hep -1 cells were over-expressed with CMTM7, the expression of E-cadherin protein was increased and N-cadherin protein was decreased, indicating CMTM7 had a migration-suppressive ability. 41 The positive correlation between the expression of CMTM2 and E-cadherin in our study further confirms the role of CMTM members in cancer metastasis.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, another study has reported CMTM7 implicated in BCR expression and survival in B-1a cells [18]. Consistent with these studies, especially a recent study by Huang ZM et al, [19] CMTM7 exogenous expression in HCC cells signi cantly decreased cell proliferation and invasion, further con rmed the relationship between CMTM7 and tumor metastasis in HCC tissues.…”
Section: Discussionsupporting
confidence: 69%
“…Next, we show that negative expression of CMTM2 may participate in the progression of hepatocellular carcinoma. Several members, such as CMTM3, CMTM4, CMTM5 and CMTM7, have been documented to exhibit tumor suppressor functions in hepatocellular carcinoma cells [ 19 22 ]. In the present study, restoring CMTM2 expression not only inhibited liver cancer cell growth via G2/M phase accumulation without inducing apoptosis, but also suppressed cell metastasis and invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%